Gastroesophageal Reflux Disease: Psychological Assessment of Children and Caregivers - Salustiano,Adriane Jacinto (2019)
Abstract Gastroesophageal Reflux Disease (GERD) with high prevalence and incidence in the pediatric population is a relevant issue in public health. The literature associates family psychosocial aspects with chronic childhood illness. The present study examined the psychological alterations and peculiarities of caregivers and of children with GERD (n = 26) and healthy children (n = 30) from 3 to 12 years of age. Instruments: Sociodemographic Questionnaire and Assessment of Risk Factors for Child Illness; Hospital Anxiety and Depression Scale; and Rutter's Child Behavior Scale (A2), all of which were administered to the caregivers. Quantitative data analysis (χ2 test, Fisher's exact test and ANOVA) was performed, respecting each instrument's respective criteria. In the group of children with GERD, we observed both a higher incidence of alcohol and/or drug use/abuse and higher levels of anxiety and depression on the part of the caregivers, as well as psychosocial problems involving the child. In light of the developmental level expected for this age group, greater frequency of behavioral problems was also observed. We thus conclude that there is a correlation between family psychological traits and GERD in children, stressing the need for conducting further studies and for supervising interdisciplinary clinical practices in the health care of this population.